Prepared for eternity : a study of human embalming techniques in ancient Egypt using computerised tomography scans of mummies - Loynes, Robert (Archaeopress Egyptology, 2015)
Robert Loynes presents analyses of 60 CT scans of ancient Egyptian human mummies, collected from museums throughout the UK and continental Europe. The effect is that of performing 'virtual autopsies', allowing techniques of mummification to be examined. The historical age of the mummies ranges from the Middle Kingdom to the Roman period. Several observations are made regarding the preparation of mummies and confirmation of previously described themes is tempered by the observation of variations probably indicating individual workshop practices